Lung Cancer: Understanding Its Molecular Pathology and the 2015 WHO Classification - Inamura, Kentaro (Frontiers in Oncology, 2017)
Lung cancer is the leading cause of cancer-related death worldwide due to late diagnoses and limited treatment interventions. Recently, comprehensive molecular profiles of lung cancer have been identified. These novel characteristics have enhanced the understanding of the molecular pathology of lung cancer. The identification of driver genetic alterations and potential molecular targets have resulted in molecular targeted therapies for an increasing number of lung cancer patients. Thus, the histopathological classification of lung cancer was modified in accordance with the increased understanding of molecular profiles. This review focuses on recent developments in the molecular profiling of lung cancer and provides perspectives on updated diagnostic concepts in the new 2015 WHO classification. The WHO classification will require additional revisions to allow for reliable, clinically meaningful tumor diagnoses as we gain a better understanding of the molecular characteristics of lung cancer.